Reflection and Reflective Teaching A Case Study of Four Seasoned Teachers in the Cayman Islands - Minott, Mark Anthony (2006)
This research was motivated by my personal desire to learn more about reflective teaching, and by the fact that a number of local researchers in the Cayman Islands highlighted the need to accumulate a body of knowledge addressing local issues in all disciplines, including teaching and learning. The purpose of this investigation was to provide a practically adequate understanding of lesson planning, implementation, and evaluation from the perspective of selected seasoned teachers in the Islands and their use of elements of reflective teaching in these areas.